Association Between Physical Activity Intensity and the Risk for Depression Among Adults From the National Health and Nutrition Examination Survey 2007–2018 - Yang, Donghui; Yang, Ming; Bai, Jianjun; Ma, Yudiyang; Yu, Chuanhua (Frontiers in Aging Neuroscience, 2022)
Abstract Objectives: It was unclear whether vigorous physical activity (VPA) provided additional benefits for depression prevention than moderate physical activity (MPA). This study aims to examine the association between the proportion of VPA to moderate to vigorous physical activity (MVPA) (a combination of VPA and MPA) and the risk for depression and explore the optimal proportion for depression prevention. Methods: This study used data from the National Health and Nutrition Examination Survey (NHANES) 2007-2018. Proportion of VPA to MVPA was calculated among those performing any MVPA. Depression was defined as those scoring 10 and above in the Patient Health Questionnaire-9 (PHQ-9). Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (95%CIs) for depression. Results: Among 26,849 participants in our study, 2501 participants were diagnosed with depression and 12,939 adults reported any MVPA. A total of 748 participants with depression were detected in those 12,939 adults. Logistic regression was conducted among 12,939 participants. Participants with greater than 33.3% to 66.7%, greater than 66.7% to 99.9%, and 100% of VPA were inversely associated with 33% (OR=0.67, 95% CI= 0.50, 0.92), 38% (OR=0.62, 95% CI= 0.40, 0.96), 35% (OR=0.65, 95% CI= 0.46, 0.91) lower risk for depression. In subgroup analyses, significant associations were only observed in men and those aged 45 years and above. Conclusion: This study revealed a higher proportion of VPA to MVPA was associated with lower risk for depression in men and those aged 45 years and above. Besides the recommendation adults should do 150 min MVPA per week, VPA should account more in MVPA among men and older adults.